Bibliometric Analysis of Sustainable Consumption Patterns and Food Waste Reduction - Loso Judijanto; Rissa Megavitry; Salwa Aulia Novitasari (West Science Interdisciplinary Studies, 2025)
Sustainable consumption and food waste reduction have become critical research areas due to their environmental, economic, and social implications. This study employs a bibliometric analysis using Scopus data and VOSviewer to examine research trends, influential publications, and global collaboration patterns in these fields. The findings reveal that sustainable development, food waste, and waste management are central themes, with growing emphasis on consumer behavior, circular economy, and supply chain efficiency. The co-authorship and country collaboration networks highlight strong regional clusters, with Europe and North America leading research efforts, while China and India are emerging as key contributors. The heatmap analysis indicates a transition from traditional environmental impact studies toward policy-driven and behavioral research approaches. Despite this progress, interdisciplinary integration and regional diversification remain key challenges, suggesting opportunities for enhanced collaboration and localized sustainability interventions. This study provides valuable insights for researchers, policymakers, and industry stakeholders to shape future strategies in sustainable food systems, waste management, and circular economy practices.